The Effect of Work Environment on Employee Work Discipline At PT. BNI (Persero) Bima Branch - Muzdalifa Muzdalifa; Jaenab Jaenab (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
Companies need to pay sufficient attention to their work environment. A conducive work environment can provide a sense of security at work, so that if an employee enjoys his work environment, employees will feel at home at work and can do good activities so that work discipline can be improved. This study aims to determine the effect of the work environment on work discipline at PT. BNI (Persero) Bima Branch. This research is associative type with quantitative data from primary data sources. The data analysis technique used is validity test, reliability test, simple regression analysis, correlation, determination test and t test. The results of the study there is a significant influence between the work environment on the work discipline of employees at PT. BNI (Persero) Bima Branch with a very strong relationship level. Keywords: Work Environment, Work Discipline